Pendidikan Anak dalam Keluarga di Era Digital - Andriyani, Isnanita Noviya (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2018)
Technological developments increasingly consistent in everyday life. Children grow along with the rapidly evolving technology, ranging from television to computers, smartphones, and digital tablet devices with various applications. The present generation of children, called "Generation Alpha" is very different from the previous generation. They spend most of their time in digital technology. Technology is part of the lives of parents and children, so there are concerns about the negative impact on very young children, especially on cognitive, motor, and social development. Research shows that parents have the most important role in creating an environment that is appropriate for children. Therefore, parents are very important to explore to be able to integrate technology tools with good education. This article deals with education in relation to the emerging context of Alpha Generation, or technology-driven generation. Strategies that benefit parents in encouraging the use of appropriate and safe technologies: a) adhering to lasting values ​​(eg respect, honesty, hard work) recognized before the digital age, b) using technology in participatory activities (eg storytelling ), c) establishing family technology contracts, d) active monitoring of digital content and time of use, and e) be role models in the use of technology, whose ultimate aim is to inform parents of confident use of technology with children , without sacrificing physical activity, real-life exploration, and personal interaction.